2015
DOI: 10.1002/jts.21999
|View full text |Cite
|
Sign up to set email alerts
|

Trauma‐Related Guilt: Conceptual Development and Relationship With Posttraumatic Stress and Depressive Symptoms

Abstract: Despite high prevalence and concerning associated problems, little effort has been made to conceptualize the construct of posttraumatic guilt. This investigation examined the theoretical model of trauma-related guilt proposed by Kubany and Watson (2003). This model hypothesizes that emotional and physical distress related to trauma memories partially mediates the relationship between guilt cognitions and posttraumatic guilt. Using path analysis, this investigation (a) empirically evaluated relationships hypoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
48
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 32 publications
(59 reference statements)
2
48
0
Order By: Relevance
“…In addition, a dismantling study of CTT is warranted to evaluate the necessity of the TRG module, which is purported to be the key mechanism of the treatment (Kubany et al, 2003(Kubany et al, , 2004Kubany & Ralston, 2008;Kubany & Watson, 2002). Because TRG is associated with PTSD caused by other types of trauma as well (e.g., Browne et al, 2015), targeting TRG more explicitly and systematically may enhance the effectiveness of treatments in other populations. Although current gold standard treatments for PTSD are very effective, there remains room for improvement as up to 50% of people who start one of the evidence-based treatments do not experience remission (Bradley et al, 2005; IOM & Committee on Treatment of Posttraumatic Stress Disorder, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a dismantling study of CTT is warranted to evaluate the necessity of the TRG module, which is purported to be the key mechanism of the treatment (Kubany et al, 2003(Kubany et al, , 2004Kubany & Ralston, 2008;Kubany & Watson, 2002). Because TRG is associated with PTSD caused by other types of trauma as well (e.g., Browne et al, 2015), targeting TRG more explicitly and systematically may enhance the effectiveness of treatments in other populations. Although current gold standard treatments for PTSD are very effective, there remains room for improvement as up to 50% of people who start one of the evidence-based treatments do not experience remission (Bradley et al, 2005; IOM & Committee on Treatment of Posttraumatic Stress Disorder, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, identifying promising leverage points for change, such as TRG, and developing and testing interventions targeting these, are critical to improving outcomes. Indeed, guilt and shame are features of other psychopathology (e.g., Browne et al, 2015) so that targeting these may be a viable transdiagnostic intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 1A depicts Kubany’s model of trauma-related guilt. Brown and colleagues (2015) recently evaluated Kubany and Watson’s (2003) model of trauma-related guilt as a predictor of PTSD and depression symptoms. They found that guilt cognitions and distress had direct effects on PTSD and depressive symptoms, whereas global guilt did not.…”
Section: Introductionmentioning
confidence: 99%
“…Although the TRGI has proven useful, the content of the distress subscale has raised concern (e.g., Browne et al, 2015). The distress subscale measures undifferentiated emotional distress related to trauma, e.g., “What happened causes me emotional pain” (Kubany et al, 1995; Kubany et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…There is also a lack of consensus over the precise relationship between guilt and the development of post-traumatic stress. Here, whereas the DSM-5 (APA, 2013) situates guilt as one of a constellation of post-traumatic stress symptoms, Lee et al (2001) and Kubany and Watson (2003) have forwarded models of trauma-related guilt that conceptualize the emotion as constitutive of a type of post-traumatic response that drives other symptoms of post-traumatic stress (Browne, Trim, Myers, & Norman, 2015).…”
Section: Introductionmentioning
confidence: 99%